Analisis Praktik Jual Beli Dengan Konsep All You Can Eat Dalam Perspektif Ekonomi Syariah (Studi Kasus: Hana Restaurant Jakarta) - Putra, Raihan Pradana; Busnetty, Ida (Yayasan Rahmat Islamiyah, 2024)
This research aims to determine the practice of buying and selling with all you can eat concept and to find out the sharia economic perspective on the practice of buying and selling with the all you can eat concept at Hana Restaurant Jakarta. Research data was obtained through observation, interviews and documentation techniques. The method used in this research is qualitative research with a literature study approach. The data sources used in the research are primary data sources which include managers, staff, consumers and muamalah jurisprudence experts related to buying and selling practices at the restaurant in question. The results of this research indicate that the practice of buying and selling all you can eat from a sharia economic perspective is legal or halal because it is in accordance with the harmony and conditions of buying and selling. Even though there is one condition that is not completely fulfilled, namely the existence of gharar on the quantity of food consumed by consumers, this gharar is light in nature so that fiqh experts state that it is still permissible. Therefore, it is still necessary to review this concept so that all aspects are in accordance with sharia.